“LES HELLENES” THROUGH THE EYES OF WOMEN TRAVELERS OF THE SEVENTEENTH, EIGHTEENTH AND NINETEENTH CENTURIES - Irene Kamberidou (THE GLOBAL CONTEXT OF THE GREEK REVOLUTION: WOMEN AS AGENTS OF CHANGE. Webinar dedicated to the BICENTENNIAL OF THE GREEK REVOLUTION (1821-2021)., 2021)
Cite as: Kamberidou, I. (2021). “Les Hellenes” through the eyes of women travelers of the seventeenth, eighteenth and nineteenth centuries. In: The Global Context of the Greek Revolution: Women as Agents of Change: Webinar dedicated to the Bicentennial of the Greek Revolution (1821-2021). The National and Kapodistrian University of Athens (NKUA), in collaboration with California State University, Sacramento (CSUS) California, 26/11/2021.  Presentation on YouTube: https://youtu.be/1p19Px3Nb6w  Μόνιμη διεύθυνση (Πέργαμος): https://pergamos.lib.uoa.gr/uoa/dl/object/2967413